The Effect of Accounting Digitalization on Operational Efficiency and Decision Making in Companies - Sapinah Sapinah; Eko Cahyo M; Hendra Saragih; Sri Imaningati (Nomico, 2024)
Accounting digitalization has become a trend that is increasingly adopted by companies as part of a broader digital transformation. This change is believed to improve operational efficiency and support faster and more accurate decision making. The purpose of this study is to analyze the effect of accounting digitalization on operational efficiency and corporate decision making. The method used in this research is a qualitative approach with in-depth interview and survey techniques in several companies in the trade, service and manufacturing sectors. The results showed that accounting digitalization has a significant positive impact on operational efficiency through process automation, reduction of human error, and more efficient document management. In addition, digitization also improves data access speed and accuracy of financial reports, which in turn supports more timely and data-driven decision-making. However, challenges in implementation, such as initial costs and employee resistance, are still obstacles that need to be overcome. The implications of this study suggest that companies should conduct careful planning and employee training to ensure a successful transition to a digital accounting system. This research also contributes to the literature in the field of accounting digitalization and provides insights for policies that support digital transformation in the business sector.